Molecular Control of Flower Colour Change in Angiosperms - Fernanda M. Rezende; Magdalena Rossi; Cláudia M. Furlan (Plants, 2025)
Floral pigmentation contributes directly to reproductive strategies and fitness by shaping pollinator behaviour, and its regulation therefore represents a critical aspect of flower development. Additionally, it is a major determinant of aesthetic and economic value in the ornamental plant industry. This review explores the genetic, biochemical, and ecological bases of floral colour change, focusing on the biosynthesis and regulation of the three major classes of plant pigments: carotenoids, flavonoids (particularly anthocyanins), and betalains. These pigments, derived from primary metabolism through distinct biosynthetic pathways, define the spatial and temporal variability of floral colouration. We discuss the molecular mechanisms underlying flower colour change from opening to senescence, highlighting pigment biosynthesis and degradation, pH shifts, metal complexation, and co-pigmentation. Additionally, we address the regulatory networks, including transcription factors (MYB, bHLH, and WDR) and post-transcriptional control, that influence pigment production. Finally, we provide a comprehensive survey of angiosperm species exhibiting dynamic petal colour changes, emphasizing how these mechanisms are regulated.